Insights Into Earthworms and Fungi: Pioneering Roles in Mitigating Global Food Scarcity and Combatting Land Degradation - Chaturvedi S.; Kumar A.; Min L.; Mohan K.; Singh N.; Kumar R. (My University, 2025)
Climate change significantly impacts terrestrial ecosystems by altering soil moisture, temperature regimes, rainfall patterns, and frequency of extreme weather events. These disruptions lead to shifts in soil community structures, accelerates land degradation processes, which in turn exacerbate the global food crisis. This review explores the roles of earthworms and fungi in improving soil health and mitigating food insecurity through their contributions to nutrient cycling, soil fertility, and plant growth. Earthworms and fungi recognized as key biological agents in nutrient cycling, soil structures enhancement, and carbon sequestration. They play crucial roles in heavy metal remediation, soil quality, fostering sustainable agricultural practices such as organic farming. The review emphasizes the influence of earthworms on nutrient dynamics, particularly in response to organic residues management, soil characteristics, and field conditions. Earthworm activity positively affects soil microbial communities, which in turn impacts plant growth, even under stress factors like soil contamination and temperature extremes. Review identifies key research gaps in the understanding of earthworm and fungi distribution, performance, and their capacity for soil remediation in varied agro-ecological contexts. In addition to biotic factors, present review also examines alternative food habits and superfoods as strategies to address zero hunger, aligning with the United Nations Sustainable Development Goals (SDGs) for zero hunger, poverty eradication, improved health, and overall well-being. By incorporating earthworms and fungi into agricultural systems and addressing critical research needs, there is significant potential to mitigate land degradation and contribute to the alleviation of global food crises. © 2025 John Wiley & Sons Ltd.